1962
DOI: 10.1071/ar9620551
|View full text |Cite
|
Sign up to set email alerts
|

Studies on resistance in calves to experimental infections with the nodular worm, Oesophagostomum radiatum (Rudolphi, 1803) Railliet, 1898

Abstract: In calves reared free of Oesophagostomum radiatum and given a single infection of this helminth, the third ecdysis in the life cycle was completed in the gut wall in 5-7 days. The fourth stage larva moved into the gut lumen between the seventh md 14th days, where the fourth ecdysis occurred between 17 and 22 days. The prepatent period was 32-42 days. Egg production reached its peak usually during the sixth to 10th weeks, and in most calves this rate of production persisted for only 1-4 weeks. The subsequent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1964
1964
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was found that there was no delay in the onset of patency, regardless of the origin of the larvae, thus indicating that immunity per se did not affect incoming worms in their development into the mature adult stage (Roberts et al 1963).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was found that there was no delay in the onset of patency, regardless of the origin of the larvae, thus indicating that immunity per se did not affect incoming worms in their development into the mature adult stage (Roberts et al 1963).…”
Section: Discussionmentioning
confidence: 88%
“…Rothwell 1989). This was demonstrated for Trichinella spiralis from mice (Kennedy and Bruce 1981), Strongyloides ratti from rats (Moqbel et al 1980), Nippostrongylus brasiliensis from mice (Henney et al 1971), and O. radiatum from calves (Roberts et al 1963). Several experiments have shown that worms on the verge of expulsion in their primary host are capable of normal survival in naive hosts (see Rothwell 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This procedure was repeated on four occasions with a different group of calves each time. Egg counts and larval cultures were performed following the methods of ROBERTS & O'SULLIVAN (1950) and ROBERTS et al, (1962). After 7 days incubation at 27°C, larvae from the cultures were harvested using the inversion method.…”
Section: Faecal Culturementioning
confidence: 99%
“…The same authors failed to infect lambs percutaneously (Shelton and Griths 1968a). Similarly, Roberts et al (1962) were unsuccessful at establishing an O. radiatum infection percutaneously in cattle and concluded that this parasite establishes only when infective larvae are ingested orally. This is in agreement with observations of larvae of O. bifurcum, the nodular worm of humans, being incapable of penetrating the skin of a volunteer (Krepel et al 1992;Polderman and Blotkamp 1995).…”
Section: Discussionmentioning
confidence: 99%